EFEKTIFITAS ANTARA TEKNIK RELAKSASI GENGGAM JARI DAN RELAKSASI NAFAS DALAM TERHADAP PENURUNAN INTENSITAS NYERI POST OPERASI APPENDIKTOMI DI RUANG EDELWEIS A RSUD KARSA HUSADA BATU - Pramudiva Kencana Wungu, Pinggan Ratu; Yuliwar, Roni; Hamarno, Rudi; Marsaid (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Appendicitis is the most common cause of acute abdominal pain, typically managed through appendectomy. Postoperative pain is a major issue that affects patient recovery. Non-pharmacological interventions, such as finger hold relaxation and deep breathing techniques, are considered effective in reducing pain intensity. Objective: This study aimed to compare the effectiveness of these two techniques. Methods: A quasi-experimental design with a two-group pre-test and post-test approach was used, involving 30 patients at Karsa Husada Batu Regional Hospital. The analysis used is the bivariate Wilcoxon Sign Rank Test and Mann Whitney U Test. Results: The results of the study showed that the level of anxiety before CA mammary surgery patients were given progressive muscle relaxation was 9(60%) seriously anxious and before the patients were given slow deep breathing 8(53.3%) were seriously anxious. After the intervention, 2 (13.3%) patients had the criteria for Severe Anxiety and in the slow deep breathing relaxation technique group 6 (40%) had the criteria for Severe Anxiety. Conclusion: Both techniques were found to be equally effective in reducing postoperative pain following appendectomy.